(untitled) (Agro Productividad, 2021)
Objective: This article aims to show the statistical density of the population per block, to know its effect as a critical spatial result and its relationship with some socio- environmental indicators, this analysis-process incorporates statistical data and geographic information systems as a model for territorial spatial analysis, which shows the relationship between demand and generation of services. Design / Methodology / Approach: The Urban Basic Geostatistical Units data of INEGI (the Spanish acronym of the National Geostatistical Information Institute in Mexico) was used on block-level as: number of inhabitants and number of dwellings. It was associated with variables identified by exploring those key stakeholders at the locality (Delegates, and the Council for Citizenship Participation (in Spanish, COPACI), as well as the Huexotla Ejido Commissariat, their clergy representative and some other key informants. In addition, GIS were used to digitize vector information and to integrate a relational database for the geospatial analysis of the variables, data and indicators in order to obtain zoning maps. Results: This study presents a proposal for the generation of socio-environmental indicators that can be used in territorial analysis with urban and rural applications using Geographic Information Systems as a tool. Study limitations: Transition processes converge in geographic transformation and, consequently have effects on landscape changes; demand for public services; and solid waste generation. Findings / Conclusions: The size of the scale used for the locality analysis contributes to determine the territorial planning of a geographical space. Thus, results obtained deliver information for planning in the decision-making processes at localities in rural to urban transitional zones.